2011
DOI: 10.1007/s00360-011-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of adaptive nonshivering thermogenesis in a marsupial, the fat-tailed dunnart (Sminthopsis crassicaudata)

Abstract: The presence of nonshivering thermogenesis in marsupials is controversially debated. Survival of small eutherian species in cold environments is crucially dependent on uncoupling protein 1 (UCP1)-mediated, adaptive nonshivering thermogenesis that is executed in brown adipose tissue. In a small dasyurid marsupial species, the fat-tailed dunnart (Sminthopsis crassicaudata), an orthologue of UCP1 has been recently identified which is upregulated during cold exposure resembling adaptive molecular adjustments of eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…The NST-capacity values were determined as the difference between the maximum VO 2 after noradrenaline injection and the basal metabolic rate (BMR) (the resting metabolic rate (RMR) in some cases) further claimed the absence of BAT in 37 other marsupial and one monotreme (prototherian) species. In addition to these morphological findings, in vivo studies found equivocal responses of typical noradrenaline-stimulated metabolic rate (Nicol 1978;Smith and Dawson 1984;Loudon et al 1985;Dawson and Olson 1988;Ye et al 1996;Nicol et al 1997;Clements et al 1998;Rose et al 1998Rose et al , 1999Opazo et al 1999;Polymeropoulos et al 2012). At this historical stage, only one study has reported on molecular hints for BAT in marsupials by immunological detection of UCP1 using heterologous eutherian antibodies (Hope et al 1997).…”
Section: Research History Of Bat Evolution Marsupialsmentioning
confidence: 82%
See 2 more Smart Citations
“…The NST-capacity values were determined as the difference between the maximum VO 2 after noradrenaline injection and the basal metabolic rate (BMR) (the resting metabolic rate (RMR) in some cases) further claimed the absence of BAT in 37 other marsupial and one monotreme (prototherian) species. In addition to these morphological findings, in vivo studies found equivocal responses of typical noradrenaline-stimulated metabolic rate (Nicol 1978;Smith and Dawson 1984;Loudon et al 1985;Dawson and Olson 1988;Ye et al 1996;Nicol et al 1997;Clements et al 1998;Rose et al 1998Rose et al , 1999Opazo et al 1999;Polymeropoulos et al 2012). At this historical stage, only one study has reported on molecular hints for BAT in marsupials by immunological detection of UCP1 using heterologous eutherian antibodies (Hope et al 1997).…”
Section: Research History Of Bat Evolution Marsupialsmentioning
confidence: 82%
“…The South American marsupial Monodelphis domestica expresses UCP1 mRNA at the juvenile stage (G), whereas adult Australian fat-tailed dunnarts possesses "brownish" adipose tissue (H, Jastroch et al 2008). However, noradrenalineinduced thermogenesis appears to be non-adaptive (Polymeropoulos et al 2012) and thermogenic functionality of marsupial UCP1 has not been demonstrated so far. In Afrotheria, BAT is thermogenically active and adaptive to ambient temperatures in elephant shrews (D, Oelkrug et al 2012) and lesser hedgehog tenrecs (F, Oelkrug et al 2013).…”
Section: Identification Of Thermogenic Bat In Modern Eutheriansmentioning
confidence: 96%
See 1 more Smart Citation
“…This process occurs through both non-shivering and shivering thermogenesis (Choi et al, 2001;Lee et al, 2010), and is characterized by high energy expenditure that approaches the upper limits for sustained aerobic metabolism (Geiser, 2004;Heldmaier et al, 2004;Peterson et al, 1990). Marsupial hibernators are unique in the sense that many species do not exhibit a robust non-shivering thermogenic response (Cortes et al, 2014;Opazo et al, 1999;Polymeropoulos et al, 2012), and as such they may be more reliant on shivering thermogenesis during arousal. Because of their much larger body mass and thermal inertia, bears display several differences in hibernation characteristics from those of small mammal hibernators.…”
Section: Hibernation Backgroundmentioning
confidence: 99%
“…Even in marsupials, members of endothermic mammals that split about 130-150 million years ago from eutherians, the role of UCP1 in adipose tissue is unclear. The molecular phylogeny groups marsupial UCP1 close to ectothermic UCP1 orthologs (29), and classical adaptive thermogenic responses are missing in marsupials despite cold induction of UCP1 (30). From the perspective of UCP1's evolutionary history starting in ectotherms, there should be more than thermogenesis, particularly in archetypal UCP1, and there is accumulating evidence that the UCP1-dependent effects on ROS regulation may have contributed to shape the integration of UCP1 into the high thermogenic capacity of eutherian BAT.…”
mentioning
confidence: 99%